Performance assessment of a wind turbine using benchmark model: fuzzy controllers and discrete adaptive LQG - Melício, Rui (2014)
High performance and reliability are required for wind turbines to be competitive within the electrical energy market. A key challenge for control is the wind power which is an unpredicted input and also acts as a disturbance. Performance assessments of a discrete adaptive LQG (linear quadratic-Gaussian) as well as a fuzzy PI (proportional-integral) control of publicly available wind turbine benchmark model are proposed. The main contribution involves a comparison of closed loop system performance and energy consumption achieved by both controllers. Simulation results by Matlab/Simulink are shown in order to illustrate the effectiveness of the design.